A Study on the Relationship between Quality of Work Life and Job Enrichment among Electricity Operators - Abbas Shirazi; Seyed Abolfazl Zakerian; Mahmood Mahmoodi (Mazandaran University of Medical Sciences, 2016)
Introduction and Purpose: Job enrichment is one of the modes of improving the employees’ quality of work life, that if properly done, the employees will enjoy high quality of work life. Therefore, the current study aimed to investigate the relationship between quality of work life and job enrichment among electricity operators in Markazi Province in 2015.Methods: This study is cross-sectional and practical. The population under investigation corresponds to a group of 80 electric power transmission operators in Markazi Province, who were selected through stratified random sampling from a set of positions available in three areas of the province. For the purpose of measuring the employees’ quality of working life and job enrichment, Van Laar and Hackman and Oldham questionnaires were used, respectively. Data analysis was performed by using descriptive statistics, chi-square test, and Fisher's exact test, using SPSS 22. Results: The results of the study demonstrated that electricity operators enjoyed average job enrichment with the mean score of 54.3% and also average quality of working life with the mean score of 54.48%. Moreover, this study revealed a direct and significant correlation between the job enrichment and quality of working life.Conclusion: Due to the low level of job enrichment and quality of work life among the operators, the current study highlighted the role of management in implementing effective interventions to improve these two mediums.